The mom & pop store how the unsung heroes of the American economy are surviving and thriving - Spector, Robert 1947- (Walker & Company, 2009)
Business journalist Spector celebrates the history of small, independent retail stores and how mom and pop businesses across the country still thrive on attentive customer service and community support.